The Exploring Pre-Serving English Teacher's Experiences on implementation of Independent Curriculum in English Learning and Teaching in Junior High School - Ratna Adita Widya Ningrum; Jen Jacob; Ratna Adita Widya Ningrum; Jen Jacob (INTENS (International Journal of English Education and Linguistics), 2024)
The curriculum is a set of structured rules that are very necessary and very important in the world of education. Indonesia has undergone curriculum changes 14 times until it finally became an independent curriculum. In implementing the independent curriculum, many phenomena explain that Pre-Service English Teachers experience many obstacles and challenges. This research was conducted to describe, explore and analyze the implementation of Pre-Service English Teachers in the independent curriculum. Apart from that, it also explains the problems (challenges and obstacles) faced during the implementation of the independent curriculum, especially at the junior high school (SMP) level. The question raised is how do Pre-service English Teachers carry out the teaching and learning process in the Independent Curriculum. And what are the challenges and obstacles of Pre-service English Teachers in implementing the Independent Curriculum. This research was conducted using descriptive qualitative research with a phenomenological approach. Data was collected by interviewing 10 participants from different universities and distributing questionnaires. As well as the results presented from interviews and questionnaires are in a descriptive form. The results of the analysis of the answers to questions that have been formulated in research. The results of this analysis are personal experiences during the implementation of the independent curriculum, the learning process carried out by the English Pre-Teacher from start to finish, the challenges and obstacles found, as well as the solutions made in facing these challenges and obstacles. Which is that the independent curriculum has many advantages and is able to support English learning activities. Then in preparation before learning activities, namely compiling teaching modules, learning outcomes, learning objectives, creating media devices, as well as assessment and project activities. Many challenges were found, of course, in the preparation of projects, class conditions, and preparation of teaching materials. In its completion, the Pre-Teacher exchanges ideas with other teachers, seeks other sources and learns to understand the concept of an independent curriculum. Keywords: Independent Curriculum, Pre-Service English Teacher, Challenges, Obstacles, Experience